Air-Stable Binary Hydrated Eutectic Electrolytes with Unique Solvation Structure for Rechargeable Aluminum-Ion Batteries - Meng, Pengyu; Huang, Jian; Yang, Zhaohui; Jiang, Min; Wang, Yibo; Zhang, Wei; Zhang, Jiao; Sun, Baode; Fu, Chaopeng (Nano-Micro Letters, 2023)
Aluminum-ion batteries (AIBs) have been highlighted as a potential alternative to lithium-ion batteries for large-scale energy storage due to the abundant reserve, light weight, low cost, and good safety of Al. However, the development of AIBs faces challenges due to the usage of AlCl3-based ionic liquid electrolytes, which are expensive, corrosive, and sensitive to humidity. Here, we develop a low-cost, non-corrosive, and air-stable hydrated eutectic electrolyte composed of aluminum perchlorate nonahydrate and methylurea (MU) ligand. Through optimizing the molar ratio to achieve the unique solvation structure, the formed Al(ClO4)3·9H2O/MU hydrated deep eutectic electrolyte (AMHEE) with an average coordination number of 2.4 can facilely realize stable and reversible deposition/stripping of Al. When combining with vanadium oxide nanorods positive electrode, the Al-ion full battery delivers a high discharge capacity of 320 mAh g−1 with good capacity retention. The unique solvation structure with a low desolvation energy of the AMHEE enables Al3+ insertion/extraction during charge/discharge processes, which is evidenced by in situ synchrotron radiation X-ray diffraction. This work opens a new pathway of developing low-cost, safe, environmentally friendly and high-performance electrolytes for practical and sustainable AIBs. Highlights: 1 A non-corrosive and air-stable hydrated eutectic electrolyte is developed. 2 The electrolyte is composed of aluminum perchlorate nonahydrate and methylurea. 3 The unique solvation structure enables reversible deposition/stripping of Al. 4 The Al-ion battery in this electrolyte shows good charge/discharge performance.